توجيهاتٌ قرآنيَّة ونبويَّة لذوي الاحتياجات الخاصَّة: حالةُ الصَّرع نموذجاً - Abdulrahman Obeid Hussein (Universiti Sains Islam Malaysia, 2026)
Journal of Quran Sunnah Education & Special Needs, Volume 9 Issue 2 Page (64–75)